Corotational elements for thin-walled laminated composite beams with large 3D rotations. (July 2020) - Mororó, Luiz Antonio Taumaturgo; Melo, Antônio Macário Cartaxo de; Parente Junior, Evandro; Lucena Neto, Eliseu; Monteiro, Francisco Alex Correia
Abstract: This work presents two finite elements for geometric nonlinear analysis of thin-walled laminated composite beams. The element cross-section properties are evaluated through a suitable thin-walled beam theory, yielding a 4×4 constitutive matrix where different couplings between generalized stresses and strains can be considered. In the local coordinate system, one element named CRL is linearly formulated, while the other element named CRTL incorporates moderate rotations. The element independent corotational approach is used in order to deal with large rotations in 3D space. Numerical experiments, considering different cross-sections and layups, demonstrate the accuracy and effectiveness of the proposed finite elements.